Business Education: Filling the Gaps in the Leader’s Awareness Concerning Organizational Phronesis - Rocha, Raysa (2021)
Education is a method of sharing social consciousness and social reconstruction. There is an existential crisis in business education driven by the conflict between social and financial objec- tives. A paradigm shift in business education requires that leaders be taught how to incorporate new competencies. Phronesis (practical wisdom), individual and collective, is an essential compe- tence to be addressed in business education. It leads companies to continuous innovation and highly sustainable performance. We conducted 23 interviews with leaders from organizations in 14 coun- tries to discuss some transformations that business education needs through leaders’ awareness concerning organizational phronesis. We conducted a thematic analysis of the interviews with sup- port from NVivo software. The results demonstrate gaps in leaders’ awareness concerning phronesis and its relationships with knowledge management and organizational spirituality. Business educa- tion still needs to be reviewed to enable leaders to learn and incorporate phronesis theory and prac- tice. Building on the gaps found in the leaders’ awareness of phronesis, we propose interdisciplinary pedagogical methods to teach business students competencies that enable the embodiment of phronesis. These changes in business education are indispensable to reach sustainability.